2018
DOI: 10.1002/jms.4252
|View full text |Cite
|
Sign up to set email alerts
|

On‐surface Fenton and Fenton‐like reactions appraised by paper spray ionization mass spectrometry

Abstract: On-surface degradation of sildenafil (an adequate substrate as it contains assorted functional groups in its structure) promoted by the Fenton (Fe /H O ) and Fenton-like (M /H O ; M = Fe , Co , Cu , Mn ) systems was investigated by using paper spray ionization mass spectrometry (PS-MS). The performance of each system was compared by measuring the ratio between the relative intensities of the ions of m/z 475 (protonated sildenafil) and m/z 235 (protonated lidocaine, used as a convenient internal standard and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In addition to iron and copper ions, other metal ions with H 2 O 2 can also form Fenton-like reactions. Augusti et al compared the efficiency of different metal ions in generating ·OH on a paper surface and found that the activity of metal ions obeyed the following order: Fe 2+ ≫ Cu 2+ > Fe 3+ , Co 2+ , Mn 2+ . Although some methods have been adopted to slow down the corrosion of transition metal species on paper by using a metal-paper isolating agent, metal complexing agent, and antioxidant, such as recombinant protein, magnesium phytate, , and 1-ethyl-3-methylimidazolium bromide (EMIMBr), , the detailed mechanism on Fenton oxidative degradation of paper is still ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to iron and copper ions, other metal ions with H 2 O 2 can also form Fenton-like reactions. Augusti et al compared the efficiency of different metal ions in generating ·OH on a paper surface and found that the activity of metal ions obeyed the following order: Fe 2+ ≫ Cu 2+ > Fe 3+ , Co 2+ , Mn 2+ . Although some methods have been adopted to slow down the corrosion of transition metal species on paper by using a metal-paper isolating agent, metal complexing agent, and antioxidant, such as recombinant protein, magnesium phytate, , and 1-ethyl-3-methylimidazolium bromide (EMIMBr), , the detailed mechanism on Fenton oxidative degradation of paper is still ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the lack of easily ionized chemical groups, general brominated organic compounds are difficult to ionize by matrix-assisted laser desorption ionization (MALDI), electrospray ionization (ESI), paper spray ionization, and other ambient ionization sources, leading to low-sensitivity in MS analysis. With the benefits of low cost, no sample pretreatment, minimal matrix effect, and high analytical efficiency, PSI-MS has been commonly used in clinical diagnosis, environmental analysis, and reaction monitoring. ,, To improve the sensitivity of weakly polar and nonpolar substances by MS detection, online derivatization of the target analytes has been integrated into PSI (termed as reactive PSI). Huang’s group quantitatively determined quinones in complex samples by reactive PSI-MS, where quinones were in situ derivatized with cysteamine to significantly improve the ionization efficiency of quinones.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we use paper spray mass spectrometry (PS-MS), because of its unique features (e.g., simplicity, low cost, and without sample pretreatment) and success in chemical reactivity assessment, to characterize the reaction mechanisms between triazine and H 2 S, as a function of the pH of the reaction solution. Evidences from experimental observations using high-resolution and tandem mass spectrometry identify the ionic species involved in the reaction procedures, and plausible mechanisms are proposed to elucidate the complex reaction inside the process.…”
mentioning
confidence: 99%